ANALISIS PENGARUH PENDAPATAN DAN TABUNGAN WADIAH TERHADAP BONUS WADIAH PADA BANK SYARIAH PERIODE (2015–2019) - Shela Indriana (Journal Tafkirul Iqtishodiyyah, 2025)
This study aims to analyze the effect of bank income and wadiah savings on wadiah bonuses in State-Owned Islamic Banks during the period 2015–2019. The significance of this research lies in understanding the key determinants of wadiah bonuses as a non-contractual incentive mechanism that plays an important role in attracting and retaining customers within the Islamic banking system. This study employs a quantitative method using multiple linear regression analysis. The sample was selected through purposive sampling and consists of two state-owned Islamic banks, namely BNI Syariah and Bank Syariah Mandiri, using secondary data obtained from annual financial reports. The findings reveal that, partially, bank income has no significant effect on wadiah bonuses, whereas wadiah savings have a positive and significant effect. Simultaneously, bank income and wadiah savings show a positive and significant influence on wadiah bonuses. These results indicate that bonus distribution policies are more strongly affected by the volume of customers’ deposited funds than by the bank’s income performance. The study implies the need for strengthening strategies to optimize wadiah fund collection as a means to enhance competitiveness among Islamic banks. The limitations of this study include the restricted sample size and the limited number of variables examined; therefore, future research is recommended to expand the sample and incorporate additional variables to provide a more comprehensive analysis.